Fuzzy logic approach for prediction the lift coefficient on an aircraft model with and without winglet - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Iqbal, Parvez; Muhidin, Arifin; Mohamad, Mazian (2009)
This paper describes the unique structure of an aircraft model with and without winglet tested at Aerodynamics Laboratory, Faculty of Engineering (University Putra Malaysia) using subsonic wind tunnel of 1000 mm × 1000 mm rectangular test section and 2500 mm long. Focusing on predicting the aerodynamic characteristics of the aircraft model, three main issues are studied in this paper. First, a six component wind tunnel external balance is used for measuring lift, drag and pitching moment. Secondly, Tests are conducted on the aircraft model with and without winglet. And thirdly, Artificial intelligence system such as fuzzy logic approach is used to predict the lift coefficient performance. Therefore, the primary purpose of this work was to investigate the relationship between lift coefficients, with free-stream velocities and angle of attacks, and to illustrate how fuzzy system might play an important role in prediction of lift coefficient with the addition of certain winglet configurations.